Comparative analysis of ELISA, FEIA and CLIA techniques in diagnostic immunoassays for thyroid stimulating hormone: A cross-sectional study form Morang, Nepal - Mallick, Ram L.; Gaire, Chandra Prakash (Journal of Biomedical Sciences, 2023)
Background: TSH and circulating thyroid hormones are measured in serum as part of a thyroid function test (TFT), which evaluates the thyroid gland's ability to produce and regulate thyroid hormones. The objective of the current study was to compare the technical performance between ELISA, FEIA and the currently marketed automated CLIA for measuring the TSH level.Material and methods: A total of 1,200 participants were enrolled in the study. Subjects were chosen randomly, either OPD patients or inpatients of Birat Medical College Teaching Hospital. Chemiluminescence Immunoassay (CLIA), Enzyme-linked Immunoassay (ELISA) and Fluorometric Enzyme Immunoassay (FEIA) technologies were performed.Results: The total number of patients (1200) was categorized into group I, normal TSH (n = 680); group II, elevated TSH (n = 300); and group III, decreased TSH (n = 220). CLIA and FEIA based results were significantly more sensitive compared to ELISA results for TSH detection.Conclusion: Chemiluminescence assay system, when compared to FEIA and ELISA, is far superior in terms of accuracy and sensitivity for reporting both subnormal and above normal TSH levels and can be helpful in the detection of subclinical thyroid dysfunction (SCTD) and in the screening of thyroid diseases.